N-Acylbenzotriazoles as Proficient Substrates for an Easy Access to Ureas, Acylureas, Carbamates, and Thiocarbamates via Curtius Rearrangement Using Diphenylphosphoryl Azide (DPPA) as Azide Donor - Yadav, Mangal S.; Singh, Sumt K.; Agrahari, Anand K.; Singh, Anoop S.; Tiwari, Vinod K. (Synthesis, 2021)
A diverse range of ureas, N-acylureas, carbamates, and thiocarbamates has been synthesized in good to excellent yields by reacting N-acylbenzotriazoles individually with amines or amides or phenols or thiols in the presence of diphenylphosphoryl azide (DPPA) as a suitable azide donor in anhydrous toluene at 110 °C for 3–4 hours. In this route, DPPA was found to be a good alternative to trimethylsilyl azide and sodium azide for the azide donor in Curtius degradation. The high reaction yields, one-pot and metal-free conditions, straightforward nature, easy handling, use of readily available reagents, and in many cases avoidance of column chromatography are the notable features of the devised protocol.
Keywords: N-acylbenzotriazoles; N-acylureas; benzotriazoles; Curtius rearrangement; diphenylphosphoryl azide; carbamates; thiocarbamates; ureas